Answered

Explore Westonci.ca, the leading Q&A site where experts provide accurate and helpful answers to all your questions. Explore our Q&A platform to find in-depth answers from a wide range of experts in different fields. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.

Simplify. Write the expression using only positive exponents. 3^−2⋅k^0⋅w^0/w^−6

Sagot :

Answer:

Step-by-step explanation:

Any variable raised to 0 is 1

⇒ [tex]a^{0}=1[/tex]

[tex]a^{-m}=\dfrac{1}{a^{m}} \\\\\dfrac{1}{a^{-m}}=a^{m}\\\\[/tex]

[tex]\dfrac{3^{-2}*k^{0}*w^{0}}{w^{-6}}=\dfrac{3^{-2}}{w^{-6}}\\\\\\=\dfrac{1}{3^{2}}*w^{6}\\\\\\=\dfrac{w^{6}}{3^{2}}[/tex]